Economic Life of Mexican Beach Vendors : Acapulco, Puerto Vallarta, and Cabo San Lucas. - Wilson, Tamar Diana (Lexington Books, 2012)
Based on the life histories of 166 beach vendors in three Mexican tourist centers-men and women whose income-generating activities form part of the informal or semi-informal economy-Economic Life of Mexican Beach Vendors explores their educational and employment aspirations and their family connections to vending. It also addresses how the vendors have been affected by the current economic recession, their residential segregation in neighborhoods far from the tourist zones, and the special cases of Indigenous and of women vendors.